2015
DOI: 10.1038/cddis.2015.129
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of radiochemoimmunotherapy-induced B16 melanoma cell death by the pan-caspase inhibitor zVAD-fmk induces anti-tumor immunity in a HMGB1-, nucleotide- and T-cell-dependent manner

Abstract: One prerequisite that radiotherapy (RT) and chemotherapy (CT) result in anti-tumor immune responses is triggering of immunogenic cell death forms such as necroptosis. The latter is inducible by inhibition of apoptosis with the pan-caspase inhibitor zVAD-fmk. The design of multimodal therapies that overcome melanoma's resistance to apoptosis is a big challenge of oncoimmunology. As hints exist that immune stimulation by hyperthermia (HT) augments the efficacy of melanoma therapies and that tumors can be sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 62 publications
1
63
0
Order By: Relevance
“…31,51 A recent study suggested that B16F10 melanoma cells can be driven into ICD in the presence of the pan-caspase inhibitor z-VAD-FMK. 54 Hence, the current results altogether suggest that there is not a single ICD pathway but multiple distinct signaling cascades that can culminate in ICD.…”
Section: Discussionmentioning
confidence: 93%
“…31,51 A recent study suggested that B16F10 melanoma cells can be driven into ICD in the presence of the pan-caspase inhibitor z-VAD-FMK. 54 Hence, the current results altogether suggest that there is not a single ICD pathway but multiple distinct signaling cascades that can culminate in ICD.…”
Section: Discussionmentioning
confidence: 93%
“…Further supporting this contention, B16 mouse melanoma cells growing in syngeneic mice exhibit an improved sensitivity to radiation therapy in the presence of Z-VAD-fmk, promoting necroptosis over apoptotic RCD and hence favoring the release of immunostimulatory DAMPs and consequent DC maturation (189). Moreover, the antineoplastic effects of Newcastle disease virus (NDV) in an orthotopic GL261 mouse glioblastoma model are associated with CALR exposure on the surface of dying cells and HMGB1 release, depend on a functional immune system, and can be abolished by Nec-1 (190).…”
Section: Pathophysiological Relevance Of Necroptosismentioning
confidence: 92%
“…Supporting this idea, some studies have shown a positive effect of caspase-inhibition in combination with chemo-or radiotherapy 119,120 . These potentiating effects may be due to various mechasnisms including inhibition of tumour vascularization and enhanced anti-tumour immunity 119,120 . Nevertheless, inhibition of caspase function may have untoward and potentially unwanted effects.…”
Section: Targeting Apoptosis -Pushing Over the Edge And Pulling Back mentioning
confidence: 93%